Information Technology & Goals of Standards-Based Instruction - Douglas A. Archbald (Arizona State University, 2001)
This article examines goals of standards-based reform in education and ways in which developments in information technology have facilitated those goals. Since standards-based reform is a rather general concept, I begin by developing a more specific formulation which I refer to as the "standards-based instruction and assessment" model. Developments in information technology over the last fifteen years have contributed in important ways to the goals of standards-based reform at the policy level, but difficult organizational and technical challenges still have to be overcome to realize more fully the goal of standards-based instruction and assessment in instructional management and practice within schools and classrooms.